An Interdisciplinarity in High School in Vocational Education (Research, Society and Development, 2020)
This article aims to present reflections on interdisciplinarity and its conceptions in the perspective of curriculum integration in high school integrated with vocational education, considering the interlocution of curricular bases for a broad and integral formation of the subject. Based on a systematic literature review, conceptual conceptions about interdisciplinarity and integrated curriculum are presented through the main authors who approach these themes in their works. In the search for an understanding of the curriculum composition of high school integrated to professional education, we seek to relate how the propositions of an interdisciplinary curriculum contribute to a perspective of overcoming a fragmented formation in relation to the formation and learning of the subject, and the discourse that permeates the teaching. of professional education in Brazil. In the studied literature we present that it is possible to face the historical educational duality from the interdisciplinary actions in the breaking of the fragmentation of the knowledge and the curricular integration, as possible movements for a formation committed to the broad development of the human being.